The study of physical and mechanical properties of tooth enamel using kinetic microindentation - Gileva, O.S.; Levitskaya, A.D.; Zuev, A.L. (Perm Federal Research Centre Journal, 2021)
The work carried out a comparative assessment of the physical and mechanical properties of tooth enamel that was healthy, demineralized, demineralized and subsequently infiltrated with a fluid composite according to a standard, modified and combined technique, completed by the lamination of the infiltrated enamel with a bioactive hybrid glass ionomer. An original in vitro model of artificial caries of human enamel was used for the study, its clinical-topographic and color-textural physical and mechanical properties correspond to the characteristics of enamel caries in vivo. Comparative analysis of the results of kinetic microindentation of enamel samples allows us to characterize the biomaterial from the standpoint of physical materials science, to determine the advantages and disadvantages of various technological options for the infiltration treatment of caries (focal demineralization) of enamel.